1978
DOI: 10.1107/s0567740878010420
|View full text |Cite
|
Sign up to set email alerts
|

Sc3Co, a new structure type related to Fe3C and Re3B by periodic unit-cell twinning

Abstract: Sc3Co, orthorhombic, Pnma, a = 13.102 (9), b = 8.624 (6), e = 5.829 (3) A, Z = 8, D x = 3.913 g cm -3, g(Mo Ka) = 107 cm -1. Least-squares refinement gave R = 0.048 for 535 independent diffractometer data which were corrected for absorption. The structure is characterized by trigonal prisms of Sc atoms which are centred by Co atoms. Centred trigonal prisms are also found in the Fe3C and Re3B structure types. Using the concept of periodic unit-cell twinning, the point positions of all three structure types can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1979
1979
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…In Figure , we show the results of applying this μ 3 acidity analysis to DFT-calibrated Hückel models for other members of this family. μ 3 -Neutralization bar graphs are plotted for 17 phases chosen to span a wide range of electronegativity differences, as well as some of the structural diversity in this family. , …”
Section: μ3-neutralization Through Binary Phase Formationmentioning
confidence: 99%
“…In Figure , we show the results of applying this μ 3 acidity analysis to DFT-calibrated Hückel models for other members of this family. μ 3 -Neutralization bar graphs are plotted for 17 phases chosen to span a wide range of electronegativity differences, as well as some of the structural diversity in this family. , …”
Section: μ3-neutralization Through Binary Phase Formationmentioning
confidence: 99%
“…(4) It was found that longer heat treatment time and higher heat treatment temperature facilitate the formation of Zr 3 Co phase. (5) The results showed that after mechanical alloying time of 16 h and optimum heat treatment (at 330 C for 60 min), nanostructured Zr 3 Co intermetallic powder was achieved. (6) The synthesized Zr 3 Co intermetallic powders showed an enhanced pumping properties and improved capacity for hydrogen sorption in contrast to the similar commercial getter.…”
Section: Discussionmentioning
confidence: 98%
“…Zr 3 Fe [12] belongs to the Re 3 B aristotype structure with base centered orthorhombic (Cmcm space group). The structure and symmetry (see Table 1) are retained upon hydrogenation (deuteration for neutron diffraction experiments) [8].…”
Section: Introductionmentioning
confidence: 99%